1994
DOI: 10.1111/j.1559-1816.1994.tb00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Efficacy, Decision‐Making, and Stages of Change: An Integrative Model of Physical Exercise1

Abstract: Exercise has important health benefits but a large proportion of the population is physically inactive. We examined the stages of readiness to exercise and their relationship to self‐efficacy, the costs and benefits of exercising, and self‐report of physical activity in a sample of Rhode Island worksites. Using a three‐step model‐building approach, exploratory principal components analyses were followed by an examination of the stages of change model with confirmatory structural equation modeling procedures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
150
2
9

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(170 citation statements)
references
References 49 publications
(20 reference statements)
9
150
2
9
Order By: Relevance
“…Surprisingly, the processes of change, which are part of the transtheoretical model of behaviour change, did not explain movement in active commuting behaviour change at six months. Other researchers 5 have been able to describe changes in process use over time but it has been recognised that the measurement of the processes of change for physical activity, which were modelled on those processes that were most frequently used in smoking cessation, does need to be improved. 4 It is suggested that the current instrument is not specific enough for active commuting.…”
Section: Management Action Structural Changesmentioning
confidence: 99%
“…Surprisingly, the processes of change, which are part of the transtheoretical model of behaviour change, did not explain movement in active commuting behaviour change at six months. Other researchers 5 have been able to describe changes in process use over time but it has been recognised that the measurement of the processes of change for physical activity, which were modelled on those processes that were most frequently used in smoking cessation, does need to be improved. 4 It is suggested that the current instrument is not specific enough for active commuting.…”
Section: Management Action Structural Changesmentioning
confidence: 99%
“…Higher exercise self-efficacy has indeed been found to be associated with advancement in stage of change (Marcus, Eaton, Rossi, & Harlow, 1994;Marcus & Owen, 1992), however, a recent meta-analysis of TTM studies in the exercise domain shows that the relationship is not linear. It appears that exercise selfefficacy is low in the early, pre-action stages, and increases to a moderate level at the later, action stages (Marshall & Biddle, 2001).…”
Section: Self-efficacymentioning
confidence: 99%
“…Se ha encontrado que las personas con mayores niveles de autoeficacia 11 se comprometen con mayor frecuencia en un programa regular de actividad física que aquellas que tienen niveles más bajos de autoeficacia 12 . Los individuos con alta autoeficacia tienen sentimientos mucho más fuertes de efectividad para realizar el ejercicio y para comprometerse a realizar una mayor cantidad de actividad física que los individuos que la tienen baja.…”
Section: Introductionunclassified